Addressing The Fatherless Challenge Through Pai: Integration Of Values Of Love, Compassion, And Noble Character - Sukma Jaya; Faridi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research aims to examine the integration strategy of values of love, compassion, and noble character in Islamic Religious Education (PAI) as an intervention for students in fatherless conditions, as well as to identify challenges and opportunities in its implementation within the context of Indonesian elementary schools. Employing a systematic literature analysis method, this research collected and critically analyzed relevant literature from various academic databases, focusing on publications from the last five years. The literature was classified based on thematic categories and analyzed using content analysis techniques with an interpretive approach to synthesize findings into a coherent analytical framework. The research findings reveal that effective integration strategy requires a comprehensive approach encompassing contextual curriculum development, innovative student-centered pedagogy, intensive mentoring programs, supportive learning environments, holistic authentic assessment, multi-stakeholder collaboration, and continuous teacher professional development. The implementation faces significant challenges including limited practitioner understanding, resource constraints, social stigma, curriculum inadequacies, and stakeholder coordination difficulties. However, substantial opportunities exist through rich Islamic traditions emphasizing compassion and social justice, educational technological innovations, growing awareness of children's mental health, community engagement potential, and pedagogical innovations. This research contributes to achieving Sustainable Development Goals, particularly SDG 4 on quality education and SDG 10 on reducing inequalities, by providing evidence-based frameworks for developing inclusive and responsive Islamic religious education that supports holistic character development of students in fatherless conditions, thereby building resilient future generations capable of breaking cycles of disadvantage and contributing to sustainable social development.